Prehistoric copper tools from the territory of Serbia - Antonović D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Around four hundreds prehistoric copper tools and weapons have been recorded in the territory of Serbia so far. They had been in use for a rather long period of time - from the end of the early phase of the Vinča culture until the Middle Bronze Age and some types of these objects even until the very beginning of the Iron Age. The copper alloyed with small quantities of arsenic, lead and tin started to appear already by the end of the Eneolithic indicating the attempts of prehistoric metallurgist to improve technical characteristics of the copper. On the copper tools from the territory of Serbia could be followed the evolution of shapes starting from the specimens, which completely imitated stone tools and which appeared in the beginning of the Early Eneolithic to the completely developed Bronze Age shapes, which confirm that prehistoric metallurgist entirely understood and accepted the advantages offered by metalworking. The analyses of metal composition have been performed on around 50% of prehistoric copper tools. Nevertheless, in spite of all relatively numerous analyses there is still no answer to the question concerning the primitive technology of copper ore processing and the metallurgical process of obtaining copper for the production of copper and sometime later the bronze artifacts.